2015
DOI: 10.1111/ajgw.12163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irrigation and rootstock onVitis vinifera(L.) cv. Shiraz berry composition and shrivel, and wine composition and wine score

Abstract: Background and Aims We investigated rootstock effects on the response of fruit and wine composition to reduced irrigation in vines growing on saline soil. Methods and Results Drip‐irrigated Shiraz vines on five rootstocks were subjected to industry standard and 30% reduced irrigation over four consecutive seasons. Fruit composition during berry shrivel and at harvest was assessed in each season and wine was made and assessed in two seasons. Rootstock and irrigation independently affected fruit anthocyanins con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…Furthermore, in a study involving several rootstocks treated with standard and reduced (30% less than standard) irrigation, Shiraz on Ramsey and 140 Ruggeri produced a significantly higher yield than Shiraz on 110 Richter at both irrigation treatments (Stevens et al ), similar to our observations and those of Hedberg et al (). Wine colour density of Shiraz wine from 110 Richter was 29% higher than that from Shiraz on Ramsey, and Na + and Cl − concentration in wine from 110 Richter was, respectively, 27 and 52% less than in wine from Ramsey (Stevens et al ), which was similar to our observations.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in a study involving several rootstocks treated with standard and reduced (30% less than standard) irrigation, Shiraz on Ramsey and 140 Ruggeri produced a significantly higher yield than Shiraz on 110 Richter at both irrigation treatments (Stevens et al ), similar to our observations and those of Hedberg et al (). Wine colour density of Shiraz wine from 110 Richter was 29% higher than that from Shiraz on Ramsey, and Na + and Cl − concentration in wine from 110 Richter was, respectively, 27 and 52% less than in wine from Ramsey (Stevens et al ), which was similar to our observations.…”
Section: Discussionsupporting
confidence: 91%
“…Soil volumetric water contents measured by time domain reflectometry (TDR) as well as by neutron probe were directly related to imposed irrigation regimes (Edwards and Clingeleffer, 2013). Moreover, similar results for reduced and fluctuated SVWC under deficit irrigation were reported by Stevens et al (2016), who found that SVWC reached 16.6, 17.4, 18.7 & 17.5 % in 2001, 2002, 2003 & 2014, respectively, when imposing 30 % irrigation cut-off. Mean midday leaf water potential (Ψ l ) data presented in Table 1 showed that Ψ l (MPa) after one day of treatments, was -1.08 and -0.98 for 100% ETc treated vines in 2011 and 2012, respectively.…”
Section: ) Soil and Vine Water Relationssupporting
confidence: 68%
“…For instance, a trial with cv. Shiraz during four consecutive seasons, where five rootstocks and two levels of water availability were compared (Stevens et al 2016), showed that variations in yield accounted for 25% of the differences in anthocyanin concentration when data were pooled across the four seasons. More clearly, in an experiment where the performance of cv.…”
Section: Challenges Related To Conferred Vigour Yield and Grape Compmentioning
confidence: 99%